Investigating The Impact of ZEP Quiz Gamified Assessment on Students’ Reading Comprehension and Perceptions - Putri Hidayatul Sylvia; Candra Hadi Asmara; Ribeh Najib Muhammad (Universitas Pahlawan Tuanku Tambusai, 2026)
Reading comprehension plays an important role in English language learning, yet students frequently experience difficulties due to limited engagement during assessment activities. While previous studies have investigated various gamified platforms, the implementation of ZEP Quiz in English education remains limited. This study examined the impact of ZEP Quiz on students’ reading comprehension and explored their perceptions toward its use. Employing a mixed-method sequential explanatory design, the study involved 32 students in each of the experimental and control groups at SMPN 1 Mantup. Data were collected through reading tests, questionnaires, and semi-structured interviews. The results showed that the experimental group’s mean score increased from 72.25 to 83.38. In addition, students demonstrated positive perceptions toward ZEP Quiz. The findings indicate that ZEP Quiz effectively enhances students’ reading comprehension and creates a more engaging and meaningful learning experience in English language learning.